Designing, Modelling and Analysis of Straight Turning Tool Geometry - Nemes, Csaba; Bodzás, Sándor (International Journal of Engineering and Management Sciences, 2018)
We execute the planning, modelling and examination of straight turning tool geometry with the help of a software in the modelling space. Our aim is to create a programme that – given some lengths and angles – calculates the corresponding geometry. It establishes that as a wireframe model in a file format that is easily transmittable to the CAD softwares of today, so any additional changes can be done there. An optimal geometry can be defined for the best possible chipping conditions using finite element simulation and with given technological parameters and material quality standard.